Submental artery island flap versus free flap reconstruction of lateral facial soft tissue and parotidectomy defects: Comparison of outcomes and patient factors. (March 2018) - Patel, Akshay V.; Thuener, Jason E.; Clancy, Kate; Ascha, Mustafa; Manzoor, Nauman F.; Zender, Chad A.
Highlights: The SIF is a good alternative to free flap reconstruction of lateral face/skull base. SIF had significantly lower operative times and decreased length of stay. We describe a vertically oriented harvest technique of SIF. Abstract: Objectives: The submental artery island flap (SIF) has recently been described in temporal bone defects. At our institution we have broadened the application of the SIF and modified the harvest technique for complex lateral facial and skull base defects. Our primary aim is to evaluate the outcomes of patients undergoing complex lateral facial soft tissue, parotidectomy, and temporal bone defects who are reconstructed with the SIF to a similar cohort undergoing free tissue transfer reconstruction. Materials and methods: Nineteen patients undergoing SIF and 54 patients undergoing free tissue flaps for oncologic lateral facial, parotidectomy and temporal bone defects were retrospectively identified. Comparative statistics were used to analyze variables between the two cohorts, specifically operative time, flap size, length of stay, regional recurrence, disease free survival, and overall survival. Results: No significant difference in demographic and disease related variables was observed. Operative time was significantly lower in SIF group with mean of 412.9 (SD 93.4) minutes compared to 544.1 (SD 139.9) minutes in free flap group. Flap size was significantly larger in free tissue transfer, 32.4 (SD 17.5) cm 2 (SIF) compared to mean area of 105.2 (SD 53.2) cm 2 (Free tissue transfer). A significant difference in length of stay was also noted between groups. There was no regional recurrence of disease in level I–III in SIF group. There was no significant difference in DFS or OS between the two groups. Conclusion: SIF is an oncologically sound option for reconstruction of lateral facial soft tissue, parotidectomy, and temporal bone defects.